Fabrication and characterization of graphene based silicon Schottky solar cell. (August 2018) - Singh, Sumitra; Powar, Sadanand; Mahala, Pramila; Majee, Subimal; Eshwar, T.; Kumar, Anil; Akhtar, Jamil
Abstract: Graphene, which is mechanically flexible, electrically conductive, and optically nearly transparent, is a promising contact material in flexible electronics and photovoltaic devices. In the present investigation, methods to obtain graphene film on silicon wafer and fabricate a graphene based Schottky solar cell have been presented. Scrutiny of atomic force microscopy (AFM) and Raman spectroscopy elucidates the formation of thin layer graphene on silicon. Further, I-V (current-voltage) characteristics of Schottky junction (graphene/silicon junction) have also been studied and presented. Highlights: Graphene synthesis by mechanical exfoliation on silicon wafer. AFM and Raman spectroscopy elucidates the formation of thin layer graphene on silicon. Fabricated a graphene based Schottky solar cell.